JUSTIFICATION OF CLASSIFICATION AND THE PRINCIPLES OF MANAGEMENT OF INNOVATIONS OF THE INDUSTRIAL ENTERPRISE AT THE PRESENT STAGE - S. Demin; L. Mikhailova; M. Cherkasov (Вестник университета)
On the basis of research of the existing domestic and foreign literature definition of the category «innovation» is given. Classification of innovations from a position of management of adaptation is offered and the new types of innovations allocated by financial result of innovative process for the industrial enterprise are revealed. The principles of management of adaptation of innovative processes in the industry are formulated.